IMPAD1 functions as mitochondrial electron transport inhibitor that prevents ROS production and promotes lung cancer metastasis through the AMPK-Notch1-HEY1 pathway. (10th August 2020) - Yang, Yi-Fang; Wang, Yen-Yun; Hsiao, Michael; Lo, Steven; Chang, Yu-Chan; Jan, Yi-Hua; Lai, Tsung-Ching; Lee, Yi-Chen; Hsieh, Ya-Ching; Yuan, Shyng-Shiou F.
Abstract: The tumor microenvironment (TME) and metabolic reprogramming have been implicated in cancer development and progression. However, the link between TME, metabolism, and cancer progression in lung cancer is unclear. In the present study, we identified IMPAD1 from the conditioned medium of highly invasive CL1-5. High expression of IMPAD1 was associated with a poorer clinical phenotype in lung cancer patients, with reduced survival and increased lymph node metastasis. Knockdown of IMPAD1 significantly inhibited migration/invasion abilities and metastasis in vitro and in vivo . Upregulation of IMPAD1 and subsequent accumulation of AMP in cells increased the pAMPK, leading to Notch1 and HEY1 upregulation. As AMP is an ADORA1 agonist, treatment with ADORA1 inhibitor reduced the expression of pAMPK and HEY1 expression in IMPAD1-overexpressing cells. IMPAD1 caused mitochondria dysfunction by inhibiting mitochondrial Complex I activity, which reduced mitochondrial ROS levels and activated the AMPK-HEY1 pathway. Collectively this study supports the multipotent role of IMPAD1 in promotion of lung cancer metastasis by simultaneously increasing AMP levels, inhibition of Complex I activity to decrease ROS levels, thereby activating AMPK-Notch1-HEY1 signaling, and providing an alternative metabolic pathway in energy stress conditions. Highlights: IMPAD1 was overexpressed in lung cancer and correlated with lymph node metastasis and poor prognosis. Knockdown of IMPAD1 expression specifically inhibited the  in vitro and in vivo  invasiveness of lung cancer cells. IMPAD1 promoted the conversion of PAP into AMP and the subsequent accumulation of AMP in lung cancer cells. IMPAD1 enhanced lung cancer invasion and metastasis through HEY1 signaling. IMPAD1 inhibited the activity of Complex I that prevents ROS production to promoting metastasis.